Quaternary Prevention: Perspectives from Primary Health Care - Cuba-Fuentes, María Sofía (2022)
Background: The practice of quaternary prevention leads to avoid unnecessary health interventions. Objective: To evaluate the relevance given to the concepts of quaternary prevention (P4), to describe the influence of training in Evidence Based Medicine on its practice and to present the barriers and facilitators of the practice of P4. The Study: Mixed methods study during 2018 and 2019. We surveyed 133 physicians working in primary care and conducted semi-structured interviews with 20 participants. The principles of phenomenology were used for transcript analysis. Findings: 94% consider the practice of P4 to be important. From our interviews, barriers, and facilitators for the practice of P4 at the first level of care were identified. Conclusion: Physicians consider the practice of quaternary prevention to be important. Relevant barriers and facilitators are the specific characteristics of the healthcare system, the patient, and the physicians.